Concepciones y reflexiones sobre calidad, evaluación y acreditación institucional (2021)
Institutions of higher education have developed strategies to improve their services offered and thus gain recognition nationally and internationally. Among all, the most recognized alternative has been the implementation of accreditation processes. This article aims to address the various concepts of processes, their implementation in different parts of the world and their strengths and weaknesses in Colombia. A literature review was conducted to obtain information about the stages and elements necessary for the implementation of accreditation processes. It was concluded that, although these processes have some gaps, they are necessary to unify the criteria for student training and institutional evaluation, which enriches the participation of the educational community.